Interference with TGFβ1-Mediated Inflammation and Fibrosis Underlies Reno-Protective Effects of the CB1 Receptor Neutral Antagonists AM6545 and AM4113 in a Rat Model of Metabolic Syndrome - Basma G. Eid; Thikryat Neamatallah; Abeer Hanafy; Hany M. El-Bassossy; Lenah Binmahfouz; Hibah M. Aldawsari; Atif Hasan; Gamal Abd El-Aziz; Kiran Vemuri; Alexandros Makriyannis (Molecules, 2021)
The role of cannabinoid receptors in nephropathy is gaining much attention. This study investigated the effects of two neutral CB1 receptor antagonists, AM6545 and AM4113, on nephropathy associated with metabolic syndrome (MetS). MetS was induced in rats by high-fructose high-salt feeding for 12 weeks. AM6545, the peripheral silent antagonist and AM4113, the central neutral antagonist were administered in the last 4 weeks. At the end of study, blood and urine samples were collected for biochemical analyses while the kidneys were excised for histopathological investigation and transforming growth factor beta 1 (TGFβ1) measurement. MetS was associated with deteriorated kidney function as indicated by the elevated proteinuria and albumin excretion rate. Both compounds equally inhibited the elevated proteinuria and albumin excretion rate while having no effect on creatinine clearance and blood pressure. In addition, AM6545 and AM4113 alleviated the observed swelling and inflammatory cells infiltration in different kidney structures. Moreover, AM6545 and AM4113 alleviated the observed histopathological alterations in kidney structure of MetS rats. MetS was associated with a ten-fold increase in urine uric acid while both compounds blocked this increase. Furthermore, AM6545 and AM4113 completely prevented the collagen deposition and the elevated expression of the TGFβ1 seen in MetS animals. In conclusion, AM6545 and AM4113, possess reno-protective effects by interfering with TGFβ1-mediated renal inflammation and fibrosis, via peripheral action.